Dimens??es e atributos que comp??em a reputa????o de entidades esportivas brasileiras - Cegalini, Vinicius Lordello (2017)
To establish a profile committed to its public should be the premise of a sports organization. The club and its athletes should join a community of people and entities that share the same purposes. Understanding how is (or is not) the reputation management of a club, it gets less thorny the search to attract talent, resources, partners and, just as important, new admirers. Sport organizations are already assimilating what is best in other market practices. As in the corporate world, the sport has been working the Reputation concepts, even though they know it. It is crucial to understand, however, if has been working properly and, consequently, it is attentive to the aspects suitable for the construction and maintenance of good reputation. This paper, through literature in major newspapers and academic journals, seeks to understand the origin of the reputation construct, its application in the corporate world, comparing it to your link in treatments within the sport. But search, fundamental and priority mapping which are the dimensions of reputation that are relevant to the sport, as well as its main attributes. Therefore, as a methodology, we have initially a State of the Art Search on the term reputation. Approaches, the consensus points to reputation as the last of the understanding of actions and results of an organization, represented by the capacity that it has to create value for its various stakeholders. In this sense, the very reputation defines the relationship of an organization with its stakeholders. Thus, following the work, there are interviews with key stakeholders in the sport market to seek the understanding of which dimensions of reputation best apply to sport. It was observed that the reputation of concepts used in theory so restricted to the corporate environment are already a reality for sports entities because, as strategic management, the issue of management is critical to the performance observed in addition to the sports part.